Evolution of the nitric oxide synthase family in vertebrates and novel insights in gill development - Annona, Giovanni; Sato, Iori; Pascual-Anaya, Juan; Osca, David; Braasch, Ingo; Voss, Randal; Stundl, Jan; Soukup, Vladimir; Ferrara, Allyse; Fontenot, Quenton; Kuratani, Shigeru; Postlethwait, John H; et al. (Proceedings. Biological sciences, 2022)
Nitric oxide (NO) is an ancestral key signalling molecule essential for life and has enormous versatility in biological systems, including cardiovascular homeostasis, neurotransmission and immunity. Although our knowledge of NO synthases (Nos), the enzymes that synthesize NO in vivo, is substantial, the origin of a large and diversified repertoire of nos gene orthologues in fishes with respect to tetrapods remains a puzzle. The recent identification of nos3 in the ray-finned fish spotted gar, which was considered lost in this lineage, changed this perspective. This finding prompted us to explore nos gene evolution, surveying vertebrate species representing key evolutionary nodes. This study provides noteworthy findings: first, nos2 experienced several lineage-specific gene duplications and losses. Second, nos3 was found to be lost independently in two different teleost lineages, Elopomorpha and Clupeocephala. Third, the expression of at least one nos paralogue in the gills of developing shark, bichir, sturgeon, and gar, but not in lamprey, suggests that nos expression in this organ may have arisen in the last common ancestor of gnathostomes. These results provide a framework for continuing research on nos genes' roles, highlighting subfunctionalization and reciprocal loss of function that occurred in different lineages during vertebrate genome duplications.
Keywords: Animals; Gills; genome duplication; Nitric Oxide Synthase; Fishes; phylogenomics; žábry; Evolution, Molecular; molekulární evoluce; ryby; vertebrate evolution; Phylogeny; gene duplication and loss; synteny; synthasa oxidu dusnatého; duplikace genu; Vertebrates; obratlovci; nos; zvířata; fylogeneze; Gene Duplication